'Rome was not built in a day'. Legal Sources and Reuse in roman times (I century BC - VI century AD) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
The number and complexities of the legal texts from the Roman world far surpass anything we have from other ancient societies, and this huge body of evidence allows chance to investigate how Roman jurists wished to regulate public and private construction activity. In particular, this paper aims at exploring how Roman authorities coped with salvage and reuse of buildings materials, focussing on the economic and organizational aspects of this practice. Proceeding chronologically and exploiting legal texts, literary and epigraphic sources and archaeology as complementary evidence, it will demonstrate how recycling has been an important feature of Roman building industry through the Republican and Imperial periods as a source of cheap building materials and a solution to problems related to the recycling and disposal of urban waste. At the same time, reuse will be considered as a crucial aspect of the general Imperial policy of exercising control over civic finances and patrimony.
Keywords: Reuse; Roman Law; Roman building industry